ANALISIS PENGARUH WORK FAMILY CONFLICT DAN AMBIGUITAS PERAN TERHADAP KINERJA KARYAWAN DENGAN STRESS KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Wanita Bagian Produksi PT. Nyonya Meneer Semarang) - Natalia, Putri; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to analyze the influence of the variables of work family conflict, role ambiguity, job stress and performance of employee on PT Nyonya Meneer Semarang. Data used in this study were collected through questionnaires and implemented to 72 female employees of PT Nyonya Meneer that work at production, who has married and have a family or a service life of more than one year based on purposive sampling method, based on the criteria specified by the researcher where samples were selected by using certain considerations. The techniques of data analysis in this research include test reliability, test validity, the classical assumptions, Path Analysis, and Sobel test to test the effect of mediation. The results of this study indicate that work family conflict has positive and significant effect on job stress, role ambiguity has no signifikan effect on job stress, work stress has negative and significant effect on the performance of employees, work family conflict has negative and significant effect on the performance of employees, role ambiguity has positive and significant effect on employee performance. In addition, job stress has negative effect in mediating the relationship between work family conflict and performance of employees and job stress has no effect in mediating the relationship between role ambiguity and performance of employees.